Prevalence and Regional Factors in the Development and Course of Allergic Diseases in Children in Southern Kyrgyzstan - Jumanalieva, Maksudakan (International Journal of Child Health and Nutrition, 2024)
Background: The prevalence of allergic diseases in children worldwide has increased rapidly over the past 30 years. This study aimed to identify regional factors influencing the development and course of allergic diseases for further prevention, control, and reduction of the risk and frequency of complications. Methods: To investigate the issue, 104 studies by different authors and countries, as well as topics related to allergy in children, air pollution, and regional factors of detection and prevalence of this disease in Kyrgyzstan, were selected. Of these, 52 studies were noted and analysed, which met the selection criteria and were of direct importance in this topic. Results: This study of allergic diseases in children found that more than 35% of children worldwide suffer from allergic diseases. Of these, allergic rhinitis occurs in 12% of children, atopic dermatitis is less common, but its incidence is 10-20%, and bronchial asthma, according to statistics, covers more than 14% of children. Conclusion: The results of the study helped to investigate the prevalence of allergic diseases relative to the region of residence, the impact of environmental pollution, geographical significance, and the effect of smoking on the development of allergies in children.